The Morality of The Prosecutor (Pancasila Moral Relations Guarantee Law Enforcement in Political Determination) - Ash-shidiqqi, M. Ellectrananda Anugerah; Zaelani, Aziz (Indonesian Journal of Social Science Research, 2024)
The purpose of this study is to determine the form of Pancasila's moral relationship as Indonesia's legal ideology in defending the prosecutor's office in the midst of political determination. In this work, a conceptual method is employed as a foundation for thinking to help answer problems that will subsequently be qualitatively investigated. The study's findings suggest that Pancasila, as Indonesia's legal ideology, can protect the prosecutor's office through moral relationships, which are reflected in the prosecutor's integrity. The consequence is that in order to achieve the objectives of justice in law enforcement, it is essential to maximize the implementation of the prosecutor's office's integration with a Pancasila worldview. Pancasila values can influence the prosecutor's office's integrity by allowing them to use their roles and powers to counter political determinism in the form of government interference.